Aberrant DNA methylation in breast cancer cells - Campoy, Emanuel Martin (2013)
The epigenome is regulated by a large number of macromolecular machines that are dynamically involved in various processes, including DNA methylation, histone modification and non-coding RNA signals, all of them working together to regulate the proper expression of the genome. Thus, in contrast with the genome, whose sequence is carefully conserved during cell life, the epigenome is highly dynamic. The epigenomic modifications are acquired during normal cell differentiation, replicated during mitosis and passed to daughter cells. A fundamental epigenetic attribute is that this plasticity occurs in response to environmental signals. It is therefore now accepted that the environment influences modifications in the cellular transcriptome through the epigenome. In developmental and evolutionary terms, the regulation of gene expression through epigenomic modifications is an advantageous shortcut and a highly conserved mechanism. However, it implies an increased risk for misregulation, as, for example, aberrant epigenomic modifications associate with the development of different human diseases, i.e. lupus, asthma, neurological diseases and cancer. Although epigenetic alterations in breast cancer have been deeply studied and discussed in the last decades, apparently contradictory results are yet often observed. Consequently, in this review, we will briefly discuss the latest findings of aberrant DNA methylation in breast tumorigenesis. Emphasis will be given to the discussion of the idea that different environments could explain paradoxical biological and pathobiological behaviors in individual patients and thus should be taken into consideration for the design and implementation of diagnosis, prognosis and predictive biomarkers.